Expression of basic fibroblastic growth factor, syndecan 1 and tumour necrosis factor α in resected acute colonic diverticulitis. (March 2014) - Tursi, A.; Elisei, W.; Giorgetti, G. M.; Inchingolo, C. D.; Nenna, R.; Picchio, M.; Giorgio, F.; Ierardi, E.; Brandimarte, G.
Abstract Aim Inflammation and fibrosis are present in both colonic diverticulitis and Crohn's disease (CD). The molecular pattern of basic fibroblastic growth factor (bFGF) and syndecan 1 (SD1) expression is altered in stenosing CD, but their expression in resected complicated colonic diverticulitis (ACD) is unknown. Method The expression of bFGF, SD1 and tumour necrosis factor α (TNF‐α) in 20 patients after resection of ACD was compared with 15 patients having a resection for CD. Analysis was conducted using real‐time reverse transcriptase polymerase chain reaction in biopsy samples. Results Lymphocytic and neutrophil inflammation scores were similar in both groups (P = 0.771 and P = 0.562). TNF‐α and bFGF expression was significantly higher in ACD than in CD (P < 0.0001 and P = 0.009). SD1 expression was similar in both groups (P = 0.841). Conclusion TNF‐α and bFGF are significantly overexpressed in ACD with respect to CD, whilst SD1 levels do not differ. The findings confirm that inflammation and its association with altered molecular patterns of mucosal healing may play an important role in the phenotype of the diseases.